He whakaturanga mo te hauora tamariki : a picture of child health : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Maori Studies at Massey University, Palmerston North, New Zealand - Waldon, John Allan (Massey University, 2008)
This research investigated the use of a self administrated health assessment questionnaire by children, and the significance of the translation from the source instrument (in English) into te reo Maori. The translation of a child health questionnaire was undertaken to produce a health survey tool that could be completed by a child over the age of 8 years in English or in te reo Maori. The questionnaire was pre-tested then used in a survey to determine both reliability and validity. The parents and caregivers of the children surveyed were also interviewed. The parent’s responses were compared with those of their children. The research undertaken has provided a new opportunity for children to take a central role in research into their own health. Children contributed as key experts, focus group participants and translators of the child questionnaire, alongside adults in some cases. Children provided a new perspective of their health and well-being by translating the questionnaire. This child-centred process added depth to the research of questionnaire validation and testing. The questionnaire was shown to perform adequately as a survey tool. New research is required in order to theorise beyond the questionnaire’s original two-factor conceptual model and to develop clinical and public health applications using a child-centred research process. The translation provided by the children demonstrated they are informed participants, who have an interest in their own health, are reliable and understand their health in a different manner to adults. This thesis argues that the direct and full involvement of participants in research that is designed to investigate their health is critical if new knowledge is to emerge. It also concludes the self administered questionnaire can be useful tools to understand the health of Maori speaking children.
Keywords: Child health; Maori; Health questionnaire; Child-centred process; Fields of Research::370000 Studies in Human Society::379900 Other Studies In Human Society::379902 Indigenous studies